Stress-Relieving Effects of Japanese Green Tea: Evaluation Using the Molar Ratio of Caffeine and Epigallocatechin Gallate to Theanine and Arginine as an Indicator - Keiko Unno; Takashi Ikka; Hiroto Yamashita; Yoko Kameoka; Yoriyuki Nakamura (Foods, 2025)
The major components of tea leaves and their infusions were analyzed for various types of green tea available in Japan in 2022. Almost all the green teas used were from the first crop, known for their high amino acid content. The amino acids theanine and arginine in green tea have been shown to reduce stress. On the other hand, epigallocatechin gallate (EGCG) and caffeine, the major components of green tea, counteract the effects of theanine and arginine. We have shown that the CE/TA ratio, which is the ratio of the molar sum of caffeine (C) and EGCG (E) to the molar sum of theanine (T) and arginine (A), can be used to evaluate the stress-relieving effects of each green tea. Green tea with a CE/TA ratio smaller than 3 can be expected to have a stress-reducing effect. The CE/TA ratios of the tea leaves and infusions of Gyokuro, Sencha, and Tamaryokucha were less than 3, indicating that these teas are expected to have stress-relieving effects. In addition, when the same tea leaves were infused repeatedly, it was found that most of the amino acids were eluted by the first and second cups; therefore, no stress-relieving effect could be expected after the third cup.